Examining the antecedents and consequences of perceived shopping value through smart retail technology. (January 2020) - Adapa, Sujana; Fazal-e-Hasan, Syed Muhammad; Makam, Sathyaprakash Balaji; Azeem, Muhammad Masood; Mortimer, Gary
Abstract: This study examines the antecedents and consequences of perceived shopping value through smart retail technology. Specifically, we propose that perceived complexity, perceived advantage, perceived novelty and perceived risk of using smart retail technologies determine consumers' perceived shopping value, which, in turn, influences their store loyalty and intentions to adopt smart retail technology. Further, we propose that consumer innovativeness moderates these relationships. Survey responses from 338 actual shoppers with prior experience of smart retail technology were used to test the research model, while structural equation modelling was used to develop the proposed hypotheses. The present study offers a better understanding of consumer adoption of smart retail technology that may help managers to develop adoption strategies for successful implementation of smart retail technology in-store.